New Distributional Record of lymnaea (Pseudosucclnea) Acuminata F. Typica (Lamark) (Mollusca: Gastropoda: Lymnaeidae) from Thar Desert (rajasthan) - Kumar, Seema; Ahmed, S. I. (Indian Forester, 1998)
No abstract